Catalytic material, preparation method thereof and application of catalytic material in electro-catalysis alcohol selective oxidation assisted hydrogen production

By using synthetic Ni2P catalytic materials in electrocatalytic alcohol-selective oxidation assisted hydrogen production, the problems of high energy consumption and slow kinetic process in the electrolytic water hydrogen production process are solved, and efficient and stable catalytic effects and the production of high value-added chemicals are achieved.

CN119824472AActive Publication Date: 2025-04-15CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510233254.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-15
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

In the current process of electrolyzing hydrogen production, the semi-reaction activation energy barrier between the anode and the cathode is high, resulting in high reaction energy consumption and slow kinetic process. Especially in the OER process, the four electron transfer loses more energy and the added value of oxygen produced is low.

Method used

A catalytic material is provided, including a conductive support, transition metal phosphide nanosheets and Ni phosphide nanoparticles, which are synthesized by hydrothermal and phosphating methods to form Ni2P nanoparticles, optimize the electronic structure of the catalyst surface, and enhance the diffusion ability of ions and electrons at the interface.

Benefits of technology

This catalytic material exhibits efficient and stable catalytic effects in electrocatalytic alcohol-selective oxidation assisted hydrogen production, reduces hydrogen production energy consumption, increases hydrogen production rate, and catalyzes the directional oxidation of alcohols to obtain high-value-added chemicals such as acids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of organic electrochemistry, in particular to a catalytic material, a preparation method of the catalytic material and application of the catalytic material in electro-catalysis alcohol selective oxidation assisted hydrogen production. The efficient and stable bimetallic-doped nickel-based metal phosphide catalytic material is synthesized through simple hydrothermal and phosphating methods, the electronic structure on the surface of the catalyst is optimized, and the active sites of the catalyst are further increased. The catalytic material is of a rough sheet structure, a three-dimensional net-shaped pore structure is formed, the diffusion capacity of ions and electrons at an interface is enhanced, the active surface area in an electrode-electrolyte contact area is effectively increased, and therefore the catalytic efficiency and the dynamic performance are improved. The catalytic material is applied to alcohol electrocatalytic oxidation assisted hydrogen evolution, renewable energy sources can be used for driving an electrocatalytic hydrogen evolution reaction, the hydrogen production energy consumption is greatly reduced, the hydrogen production rate is increased, and meanwhile, high-added-value chemicals such as acids are obtained by catalyzing alcohol directional oxidation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of organic electrochemistry, in particular to a catalytic material and a preparation method thereof, and application thereof in electrocatalytic alcohol selective oxidation-assisted hydrogen production. Background Art

[0002] Since the Industrial Revolution, with the rapid development of economy and the progress of social civilization, human beings have an increasing demand for energy. The large-scale use of fossil fuel resources such as coal has brought about a series of negative effects such as greenhouse effect and environmental pollution. my country's current energy consumption is highly dependent on fossil energy, and the carbon emission base is large. Therefore, vigorously developing technology has become a top priority for industries such as steel, petroleum, and chemicals.

[0003] Hydrogen has a high energy density (140 MJ / kg) and is indispensable as a clean and efficient energy source in decarbonization and sustainable energy systems. Modern hydrogen production technologies are mainly divided into three categories: clean energy water electrolysis hydrogen production, fossil fuel reforming hydrogen production, and industrial by-product hydrogen. The electrocatalytic water decomposition hydrogen production process is called green hydrogen because it has no carbon emissions. Green hydrogen technology is becoming an important technical support for achieving decarbonization goals and will be an effective response to the intermittent problem of renewable energy.

[0004] There are currently two major problems with hydrogen production by water electrolysis. The first is the high capital cost. In the process of electrocatalytic water splitting, the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode produce oxygen (O2) and hydrogen (H2), respectively. The catalyst with the best HER performance is currently Pt-based catalysts; the catalyst with the best OER performance is precious metal oxides such as Ru and Ir. Precious metal materials are very expensive, so in recent years, a lot of research work has been focused on the study of non-precious metal-based catalysts, including their oxides, hydroxides, nitrides, phosphides and other catalysts, to reduce the cost of hydrogen production. The second major problem is the high energy consumption of the reaction. The activation energy barriers of the two half reactions of the anode and cathode are high. The theoretical thermodynamic requirements of the reaction can only be achieved when the input energy is 237.2 KJ / mol, and the kinetic process of the reaction is also very slow. Especially in the OER process, the complex four-electron transfer will lose a lot of energy, and the added value of the oxygen produced is low. Using a more thermodynamically favorable organic oxidation reaction instead of the oxygen evolution reaction is an effective way to solve the above problems. This method reduces the production of oxygen and reduces the safety hazards caused by mixing with hydrogen.

[0005] Among organic oxidation reactions, biomass electrooxidation reaction (BEOR) has attracted much attention in recent years. Among them, small molecule biomass platform organics such as pentahydroxymethylfurfural, glycerol, and benzyl alcohol are considered to be the most promising oxidation substrates. Among these organics, benzoic acid, the oxidation product of benzyl alcohol, has a wide range of applications in fragrances, preservation, and medicine, and the electrooxidation process of benzyl alcohol is milder and greener than the industrial toluene oxidation process. Therefore, it is of great significance to develop efficient non-precious metal-based catalyst materials for the electrooxidation reaction of benzyl alcohol and improve its application in electrocatalytic assisted hydrogen evolution. Summary of the invention

[0006] In view of this, the technical problem to be solved by the present invention is to provide a catalytic material and a preparation method thereof and an application in electrocatalytic selective oxidation of alcohols to assist hydrogen production. The catalytic material provided by the present invention has a high catalytic effect for electrocatalytic selective oxidation of alcohols to assist hydrogen production.

[0007] The present invention provides a catalytic material, comprising:

[0008] Conductive carrier;

[0009] A transition metal phosphide nanosheet disposed on the conductive support; the transition metal phosphide is composed of Ni phosphide and a second transition metal phosphide, and the second transition metal phosphide is selected from at least two of Fe phosphide, Mo phosphide or Co phosphide;

[0010] Ni phosphide nanoparticles are disposed on the transition metal phosphide nanosheets.

[0011] The catalytic material provided by the present invention comprises a conductive carrier, which plays a supporting and conductive role. In certain embodiments of the present invention, the conductive carrier is selected from foamed nickel, carbon cloth or foamed copper.

[0012] The catalytic material provided by the present invention also includes transition metal phosphide nanosheets disposed on the conductive carrier. Specifically, the transition metal phosphide nanosheets are vertically staggered on the conductive carrier to form a nanoarray structure, and the transition metal phosphide is composed of Ni phosphide and a second transition metal phosphide, and the second transition metal phosphide is selected from at least two of Fe phosphide, Mo phosphide or Co phosphide. Preferably, the second transition metal phosphide is selected from Fe phosphide and Mo phosphide; or, the second transition metal phosphide is selected from Fe phosphide and Co phosphide. The doping amount of the transition metal atoms in the present invention is 20 wt%~60 wt%. The thickness of the nanosheets in the present invention is 15 nm~20 nm. The catalytic material provided by the present invention also includes Ni phosphide nanoparticles disposed on the transition metal phosphide nanosheets.

[0013] The present invention also provides a method for preparing a catalytic material, comprising the following steps:

[0014] S1) subjecting a conductive support to a hydrothermal reaction in a Ni salt, a transition metal salt, urea and ammonium fluoride to obtain a precursor; the transition metal salt is selected from at least two of a Fe salt, a Mo salt or a Co salt;

[0015] S2) In a protective atmosphere, the precursor obtained in step S1) is phosphated to obtain a catalytic material.

[0016] The present invention firstly conducts a hydrothermal reaction of a conductive carrier in Ni salt, transition metal salt, urea and ammonium fluoride to obtain a precursor. Specifically, Ni salt, transition metal salt, urea, ammonium fluoride and water are mixed and dispersed to obtain a precursor solution; the conductive carrier is placed in the precursor solution for hydrothermal reaction, and the conductive carrier after the reaction is dried to obtain a precursor. The temperature of the hydrothermal reaction of the present invention is 80°C~160°C; the time of the hydrothermal reaction is 4 h~10 h.

[0017] The Ni salt of the present invention is selected from one or more of Ni chloride or Ni nitrate. In certain embodiments of the present invention, the Ni salt is selected from one or more of nickel chloride or nickel nitrate. The transition metal salt of the present invention is selected from at least two of Fe salt, Mo salt or Co salt; the transition metal salt is selected from one or more of transition metal chloride or transition metal nitrate. The molar ratio of Ni ions in the Ni salt of the present invention, transition metal ions in the transition metal salt, urea and ammonium fluoride is (0.1~5): (0.2~10): (1~10): (0.2~5), preferably (0.1~1.5): (0.2~1): (1~10): (0.2~2.5), more preferably (0.5~1.5): (0.2~1): (5~10): (1~2.5).

[0018] Preferably, the transition metal salt of the present invention comprises an Fe salt and a second transition metal salt; the second transition metal salt is selected from a Mo salt or a Co salt; the Fe salt is selected from one or more of Fe chlorides or Fe nitrates; the Mo salt is selected from one or more of Mo inorganic sodium salts or Mo inorganic ammonium salts. In certain embodiments of the present invention, the Fe salt is selected from one or more of ferric nitrate or ferric chloride; the Mo salt is selected from one or more of sodium molybdate or ammonium molybdate; the Co salt is selected from one or more of cobalt nitrate or cobalt chloride. The molar ratio of Ni ions in the Ni salt of the present invention, Fe ions in the Fe salt, transition metal ions in the second transition metal salt, urea and ammonium fluoride is (0.1-5): (0.1-5): (0.1-5): (1-10): (0.2-5), preferably (0.1-1.5): (0.1-0.5): (0.1-0.5): (1-10): (0.2-2.5), more preferably (0.5-1.5): (0.1-0.5): (0.1-0.5): (5-10): (1-2.5).

[0019] After obtaining the precursor, the present invention performs phosphating on the obtained precursor in a protective atmosphere to obtain a catalytic material. Specifically, in a protective atmosphere, the phosphorus source and the obtained precursor are phosphated by heat treatment to obtain the catalytic material of the present invention. The phosphating temperature of the present invention is 300° C. to 500° C.; and the phosphating time is 2 to 4 hours.

[0020] The present invention also provides the use of the catalytic material described in any of the above technical solutions or the catalytic material obtained by the preparation method described in any of the above technical solutions in electrocatalytic selective oxidation of alcohols to assist hydrogen production.

[0021] Specifically, the present invention provides the use of the catalytic material described in any of the above technical solutions or the catalytic material obtained by the preparation method described in any of the above technical solutions as an anode catalyst in the electrocatalytic selective oxidation of alcohols to assist hydrogen production.

[0022] More specifically, an aqueous solution of an alkali metal hydroxide of an alcohol is used as an electrolyte solution, and the electrolyte solution is electrolyzed through a cathode and an anode; the anode is a catalytic material described in any of the above technical solutions or a catalytic material obtained by the preparation method described in any of the above technical solutions. The alcohols in the electrolyte solution of the present invention are selected from one or more of methanol, ethanol, benzyl alcohol and glycerol; the concentration of the alcohols in the alcohol solution is greater than or equal to 10 mmol / L. The pH value of the electrolyte solution of the present invention is 10~14. The voltage of the electrocatalytic alcohol selective oxidation assisted hydrogen production of the present invention is 1~2Vvs.RHE.

[0023] The present invention provides a catalytic material and a preparation method thereof and an application thereof in electrocatalytic alcohol selective oxidation assisted hydrogen production. The present invention synthesizes an efficient and stable bimetallic doped nickel-based metal phosphide catalytic material by simple hydrothermal and phosphating methods, and dopes phosphorus into amorphous nanosheets by annealing to form Ni2P nanoparticles, optimize the electronic structure of the catalyst surface, and further increase the active sites of the catalyst. The catalytic material presents a relatively rough sheet structure, which is staggered and connected to each other after phosphating to form a three-dimensional mesh pore structure, which enhances the diffusion capacity of ions and electrons at the interface, effectively increases the active surface area in the electrode-electrolyte contact area, and thus improves the catalytic efficiency and kinetic performance. The catalytic material of the present invention is used in the electrocatalytic oxidation assisted hydrogen evolution of alcohols, which helps renewable energy drive the electrocatalytic hydrogen evolution reaction, greatly reduces the energy consumption of hydrogen production and increases the hydrogen production rate, and at the same time catalyzes the directional oxidation of alcohols to obtain high value-added chemicals such as acids. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is an X-ray diffraction pattern of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention;

[0025] Figure 2 is a scanning electron microscope image of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention;

[0026] Figure 3 is a transmission electron microscope image of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention;

[0027] Figure 4 This is the XPS spectrum of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention;

[0028] Figure 5 is a polarization curve diagram of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention at a scanning rate of 5 mV / s;

[0029] Figure 6 Polarization curves of the catalysts obtained in Examples 1 and 2 and Comparative Examples 1 to 3 of the present invention in 1 M KOH + 10 mM benzyl alcohol;

[0030] Figure 7 This is a liquid chromatogram of the product obtained after the catalytic reaction of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention;

[0031] Figure 8 The conversion rate, selectivity diagram and Faraday efficiency diagram of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention;

[0032] Fig. 9 This is a stability test chart of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] The present invention discloses a catalytic material and a preparation method thereof and an application thereof in electrocatalytic alcohol selective oxidation assisted hydrogen production. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art and they are all deemed to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0034] The reagents used in the following examples are all commercially available; the specifications of the nickel foam used are battery grade.

[0035] The present invention will be further described below in conjunction with embodiments:

[0036] Example 1

[0037] (1) A 2 cm × 4 cm nickel foam was ultrasonically treated in a 3 M HCl solution for 15 min, rinsed with excess anhydrous ethanol, and then ultrasonically treated in anhydrous ethanol for 15 min. After the ultrasonic treatment, it was repeatedly rinsed with excess deionized water and dried in a vacuum drying oven at 60 °C for 12 h to remove impurities on the surface of the nickel foam, thereby obtaining the pretreated nickel foam.

[0038] (2) Weigh 1.5 mmol nickel nitrate hexahydrate, 0.5 mmol iron nitrate nonahydrate, 0.5 mmol sodium molybdate dihydrate, 10 mmol urea and 2.5 mmol ammonium fluoride and dissolve them in 40 mL deionized water. Stir for 20 min to completely dissolve them and transfer them to a hydrothermal reactor with a Teflon lining. Then, vertically place the pretreated nickel foam obtained in (1) into the reactor and heat it in a forced air drying oven at 120°C for 6 h. Remove the nickel foam from the hydrothermal reactor, wash it with distilled water and ethanol, and vacuum dry it at 60°C for 12 h to obtain a hydrothermal precursor.

[0039] (3) The precursor material obtained in (2) was phosphated in a tube furnace using 0.8 g of NaH2PO2·H2O powder as a phosphorus source at 300°C under an argon atmosphere for 2 h. After cooling to room temperature, the catalyst was taken out and washed with ethanol. The catalyst was then placed in a vacuum drying oven at 60°C and vacuum dried to obtain a molybdenum-doped nickel-based metal phosphide catalyst, denoted as Mo-NiFeP / NF.

[0040] Example 2

[0041] On the basis of Example 1, sodium molybdate dihydrate was replaced with cobalt nitrate hexahydrate, and the other conditions remained unchanged, thereby finally obtaining a cobalt-doped nickel-based metal phosphide catalyst, which was recorded as Co-NiFeP / NF.

[0042] Comparative Example 1

[0043] On the basis of Example 1, sodium molybdate dihydrate was not added, and other conditions remained unchanged, thereby obtaining a nickel-based metal phosphide catalyst free of molybdenum, which was recorded as NiFeP / NF.

[0044] Comparative Example 2

[0045] On the basis of Example 1, sodium molybdate dihydrate was replaced with aluminum nitrate nonahydrate, and the other conditions remained unchanged, thereby finally obtaining an aluminum-doped nickel-based metal phosphide catalyst, which was recorded as Al-NiFeP / NF.

[0046] Comparative Example 3

[0047] On the basis of Example 1, sodium molybdate dihydrate was replaced with manganese chloride tetrahydrate, and the other conditions remained unchanged, thereby finally obtaining a manganese-doped nickel-based metal phosphide catalyst, which was recorded as Mn-NiFeP / NF.

[0048] Crystal structure analysis of samples:

[0049] Use an EMPYREAN model X-ray powder diffractometer to perform XRD spectrum scanning on the molybdenum-doped nickel-based metal phosphide catalyst and the reference material obtained in Example 1. The specific operation process and equipment parameters are as follows: Cut the prepared molybdenum-doped nickel-based metal phosphide catalyst material into a small piece, stick it to a test disk with tape and place it on the XRD sample table to perform XRD spectrum scanning. Since the intensity of the diffraction peak of the nickel foam is too large to cover up the similar sample diffraction peak, the catalyst is placed in anhydrous ethanol for ultrasound, and the solution is dripped onto the test disk for testing. The scanning parameters are as follows: the scanning range is 5°~90°, and the scanning speed is 5° / min. Figure 1 As shown, Figure 1 is the X-ray diffraction pattern of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention. Figure 1 It can be seen that Mo-NiFeP / NF has Ni2P (PDF#74-1385) diffraction peaks at (111) plane (40.7°), (201) plane (44.6°), (210) plane (47.4°), (300) plane (54.2°), (211) plane (55.0°) and (400) plane (74.8°), but the peak intensity is weak, which is due to the low crystallinity or the amorphous state.

[0050] Characterization of sample morphology:

[0051] The German Zeiss GeminiSEM300 field emission scanning electron microscope was used to prepare the test sample as follows: the molybdenum-doped nickel-based metal phosphide catalyst material obtained in Example 1 was adhered to the conductive glue on the test plate, placed on the test table, and the morphology was observed after adjusting the parameters to obtain the scanning electron microscope image as shown below: Figure 2 As shown, Figure 2 This is a scanning electron microscope image of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention. Figure 2 It can be seen that the Mo-doped NiFeP layer presents a relatively rough flaky structure, which is interlaced and connected with each other after phosphating to form a three-dimensional mesh pore structure. This unique pore system not only maintains the original porosity, but also further enhances the diffusion capacity of ions and electrons at the interface, effectively increasing the active surface area in the electrode-electrolyte contact area, thereby improving the catalytic efficiency and kinetic performance.

[0052] Using a Tecnai F20 field emission transmission electron microscope, the test sample preparation method is as follows: the catalyst grown in situ on nickel foam is placed in anhydrous ethanol for ultrasonication, and the solution is dropped onto a copper sheet for testing. Figure 3 As shown, Figure 3 This is a transmission electron microscope image of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention. Figure 3 It shows that Mo-NiFeP / NF still maintains a lamellar structure after phosphating, and the formation of Ni2P nanoparticles on the surface can be clearly seen, which is consistent with the morphology observed in the SEM and HRTEM images.

[0053] X-ray photoelectron spectroscopy (XPS) of samples:

[0054] The XPS spectra of the samples were measured using the American Thermo Fisher Nexsa, and the basic vacuum of the instrument was 3×10 -9 mbar, power 300 W. When processing data, the C 1s peak of contaminated carbon is used to perform energy correction on XPS. Then, by comparing with the standard spectrum and using XPSPEAK software to perform peak fitting on the full spectrum of XPS and the high-resolution spectrum of the main metal elements, the valence state of the elements and the bonding relationship between the elements are preliminarily determined, and the XPS energy spectrum of the molybdenum-doped nickel-based metal phosphide catalyst is obtained, such as Figure 4 As shown, Figure 4 This is the XPS spectrum of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention. Figure 4It can be seen that the surface of the molybdenum-doped nickel-based metal phosphide sample is mainly composed of Ni, Fe, Mo, P, O and C elements. At the same time, the movement of each peak position indicates that the doping of P element can effectively adjust the chemical environment of the metal site and may have a positive effect on the catalytic ability. Doping with Mo is beneficial to accelerate electron transfer and optimize the adsorption of protons.

[0055] OER and BOR polarization curves of electrode materials:

[0056] The molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 was used as the working electrode, and then the Ag / AgCl electrode and the Pt sheet were used as the reference electrode and the counter electrode, respectively. 1 M potassium hydroxide solution and 10 mM benzyl alcohol (BA) were used as the electrolyte and the electrolyte, respectively, and compared with the solution without 10 mM BA. The test was carried out on a Shanghai Chenhua CHI760E electrochemical workstation at a scan rate of 5 mV / s. Figure 5 As shown, Figure 5 The polarization curve of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention at a scanning rate of 5 mV / s is shown in Figure 1. The Mo-NiFeP / NF is subjected to a 10 mA cm- -2 and 100 mA cm -2 The potentials at the current density were 1.355 V vs. RHE and 1.381 V vs. RHE, respectively, which were 31 mV lower than the OER potential in the potassium hydroxide solution without benzyl alcohol (10 mA cm -2 ) and 55 mV (100 mA cm -2 ).

[0057] BOR polarization curves of electrode materials and control samples:

[0058] The catalysts obtained in Examples 1 and 2 and Comparative Examples 1 to 3 were used as working electrodes, and then the Ag / AgCl electrode and the Pt sheet were used as the reference electrode and the counter electrode, respectively. 1 M potassium hydroxide solution and 10 mM benzyl alcohol (BA) were used as the electrolyte and the electrolyte, respectively. The test was carried out on a Shanghai Chenhua CHI760E electrochemical workstation at a scan rate of 5 mV / s. Figure 6 As shown, Figure 6 The polarization curves of the catalysts obtained in Examples 1 and 2 and Comparative Examples 1 to 3 of the present invention in 1 M KOH + 10 mM benzyl alcohol are shown in FIG. Figure 6 It can be seen that Mo-NiFeP / NF has a -2 and 100 mA cm -2The potentials at the current density were 1.361 Vvs.RHE and 1.406 Vvs.RHE respectively; Co-NiFeP / NF at 10 mA cm -2 and 100 mA cm -2 The potentials at the current density were 1.375 Vvs.RHE and 1.425 Vvs.RHE, respectively, and both performed better than NiFeP / NF (1.394 Vvs.RHE (10 mA cm -2 ), 1.535 Vvs.RHE (100 mA cm -2 ))), Al-NiFeP / NF (1.462 Vvs.RHE (10mA cm -2 ), 1.619 Vvs.RHE (100 mA cm -2 ))) and Mn-NiFeP / NF (1.369 Vvs.RHE (10 mA cm -2 ), 1.576 Vvs.RHE (100 mA cm -2 ))).

[0059] Liquid chromatogram of electrode material:

[0060] Agilent 1260 semi-preparative liquid chromatography was used to perform qualitative and quantitative analysis on the products after BOR test. Figure 7 As shown, Figure 7 The liquid chromatogram of the product obtained after the catalytic reaction of the platinum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention. The conversion rate of benzyl alcohol and the yield of benzoic acid continue to increase with the increase of time, and the intermediate product benzaldehyde is also detected at the beginning and reaches the maximum value at 1000 s, but it does not accumulate in the oxidation process, indicating that benzaldehyde is quickly oxidized to benzoic acid. When the reaction time is 5000 s, the reactant is almost completely converted, the conversion rate of benzyl alcohol reaches 99%, and the selectivity of benzoic acid is close to 98.5%.

[0061] Conversion rate, selectivity and Faraday efficiency diagram of electrode materials:

[0062] An H-type electrolytic cell with two chambers separated by a Nafion 117 membrane was used to test the electrochemical performance and collect experimental data. An Ag / AgCl (3 M KCl) electrode was used as a reference electrode, a platinum sheet was selected as a counter electrode, the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 was used as a working electrode, and a 1 M potassium hydroxide solution containing 10 mM benzyl alcohol was used as an electrolyte. The chronoamperometric test was repeated six times at a potential of 0.4 V vs. Ag / AgCl to obtain the conversion rate, selectivity graph, and Faraday efficiency graph of the molybdenum-doped nickel-based metal phosphide catalyst, as shown in FIG. Figure 8 As shown, Figure 8 The conversion rate, selectivity and Faraday efficiency of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention are shown in FIG. Figure 8 It can be seen that after six consecutive tests, the catalyst still maintained a high benzyl alcohol conversion rate and a high selectivity for benzoic acid.

[0063] Stability of electrode materials:

[0064] The stability of benzyl alcohol electrooxidation was evaluated by repeated it tests. The experiment was terminated when the constant current test time was 5000s and the cycle was repeated 6 times. The long-term stability of the molybdenum-doped nickel-based metal phosphide sample was verified in a 1 M potassium hydroxide solution containing 10 mM benzyl alcohol. The stability test graph is shown in Fig. 9 As shown, Fig. 9 This is a stability test diagram of the molybdenum-doped nickel-based metal phosphide catalyst obtained in Example 1 of the present invention. Fig. 9 It can be seen that after 6 cycles, the LSV curve of this electrode material does not change much, indicating that it has good stability and good electro-oxidation ability of benzyl alcohol.

[0065] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A catalytic material, characterized in that: include: Conductive carrier; transition metal phosphide nanosheets disposed on the conductive support; The transition metal phosphide is composed of Ni phosphide and a second transition metal phosphide, and the second transition metal phosphide is selected from at least two of Fe phosphide, Mo phosphide or Co phosphide; Ni phosphide nanoparticles are disposed on the transition metal phosphide nanosheets.

2. The catalytic material according to claim 1, characterized in that The second transition metal phosphide is selected from Fe phosphide and Mo phosphide; Alternatively, the second transition metal phosphide is selected from Fe phosphide and Co phosphide.

3. The catalytic material according to claim 1, characterized in that The doping amount of the transition metal atoms is 20 wt% to 60 wt%.

4. The catalytic material according to claim 1, characterized in that The thickness of the nanosheet is 15 nm to 20 nm.

5. A method for preparing a catalytic material, characterized in that: The following steps are involved: S1) subjecting a conductive support to a hydrothermal reaction in a Ni salt, a transition metal salt, urea and ammonium fluoride to obtain a precursor; the transition metal salt is selected from at least two of a Fe salt, a Mo salt or a Co salt; S2) In a protective atmosphere, the precursor obtained in step S1) is phosphated to obtain a catalytic material.

6. The preparation method according to claim 5, characterized in that: In step S1), the transition metal salt includes an Fe salt and a second transition metal salt; The second transition metal salt is selected from Mo salt or Co salt.

7. The preparation method according to claim 6, characterized in that: In step S1), the molar ratio of Ni ions in the Ni salt, Fe ions in the Fe salt, transition metal ions in the second transition metal salt, urea and ammonium fluoride is (0.1-5): (0.1-5): (0.1-5): (1-10): (0.2-5).

8. The preparation method according to claim 5, characterized in that: In step S1), the temperature of the hydrothermal reaction is 80°C to 160°C; the time of the hydrothermal reaction is 4 h to 10 h.

9. The preparation method according to claim 5, characterized in that: In step S2), the phosphating temperature is 300°C to 500°C; and the phosphating time is 2 to 4 hours.

10. Use of the catalytic material according to any one of claims 1 to 4 or the catalytic material obtained by the preparation method according to any one of claims 5 to 9 in electrocatalytic selective oxidation of alcohols to assist hydrogen production.

Citation Information

Patent Citations

  • Iron-doped bimetal phosphide electrocatalyst and preparation method and application thereof

    CN109174162A

  • Ruthenium-doped bimetallic phosphide catalyst, preparation method thereof and application of ruthenium-doped bimetallic phosphide catalyst in electro-catalysis alcohol selective oxidation assisted hydrogen production

    CN117488351A

  • Nickel-based bimetallic phosphide catalyst as well as preparation method and application thereof

    CN118957652A

  • Transition metal phosphide catalyst as well as preparation method and application thereof

    CN119265607A

  • Transition metal-doped nickel phosphide nanostructure, method for preparing same, and catalyst for electrochemical water decomposition including transition metal-doped nickel phosphide nanostructure

    US20230002922A1